2020
DOI: 10.1101/2020.01.23.916726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling the epidemic trend of the 2019 novel coronavirus outbreak in China

Abstract: We present a timely evaluation of the Chinese 2019-nCov epidemic in its initial phase, where 2019-nCov demonstrates comparable transmissibility but lower fatality rates than SARS and MERS. A quick diagnosis that leads to case isolation and integrated interventions will have a major impact on its future trend. Nevertheless, as China is facing its Spring Festival travel rush and the epidemic has spread beyond its borders, further investigation on its potential spatiotemporal transmission pattern and novel interv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
187
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(207 citation statements)
references
References 2 publications
14
187
2
4
Order By: Relevance
“…Fortunately, a main trend is that the estimated R 0 value for 2019-nCoV is getting reduced as case information accumulates. And with the control measures implemented, the effective reproduction number (R e ) has been shown to drop to 2.08 (1.99e2.18) as of 22 Jan 2020 [14].…”
Section: Transmissibility Of 2019-ncovmentioning
confidence: 99%
“…Fortunately, a main trend is that the estimated R 0 value for 2019-nCoV is getting reduced as case information accumulates. And with the control measures implemented, the effective reproduction number (R e ) has been shown to drop to 2.08 (1.99e2.18) as of 22 Jan 2020 [14].…”
Section: Transmissibility Of 2019-ncovmentioning
confidence: 99%
“…[8] is much higher than the estimate made by the present theoretical model. This is due to the neglect of the infectious ability of patient in latent period in previous models [6][7][8] . Because only the infected are transmissible, the actual probability of infection needs to be overestimated to adequately fit the raw data, which ultimately leads to overestimation of the number of infected people.…”
Section: Figure1 Modified Seir Propagation Dynamics Modelmentioning
confidence: 99%
“…In addition, the shortcomings of the transmission dynamic model itself have also become the direct cause of limiting its prediction effect. Latent patients are not easy to be effectively quarantined, and recent evidence shows that latent patients have a strong infectious ability, but the existing epidemic transmission dynamic models [5][6][7][8] often ignore the transmission risks caused by patients in the latent period. In addition, researchers have found that estimates of the average latency of 2019-nCoV are also changing.…”
mentioning
confidence: 99%
“…Several studies have described the epidemiological and clinical characteristics of NCP, and have demonstrated that it can transmitted between humans (4,6). A few studies have also estimated the basic reproduction number (R0) of NCP (6)(7)(8)(9)(10)(11). For instance, Li et al computed the R0 of 2.2 using daily NCP data before January 4 in Wuhan.…”
Section: Introductionmentioning
confidence: 99%